2020
DOI: 10.1063/5.0015094
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the structural motifs present in small ammonium and aminium bisulfate clusters of relevance to atmospheric new particle formation

Abstract: Atmospheric new particle formation is the process by which atmospheric trace gases, typically acids and bases, cluster and grow into potentially climatically relevant particles. Here, we evaluate the structures and structural motifs present in small cationic ammonium and aminium bisulfate clusters that have been studied both experimentally and computationally as seeds for new particles. For several previously studied clusters, multiple different minimum-energy structures have been predicted. Vibrational spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 73 publications
2
39
0
Order By: Relevance
“…Scaling harmonic frequencies or calculating anharmonic frequencies is critical for spectroscopists who are trying to locate hydrogen-bonded molecular clusters in their experiments. ,, Yet, previous work has indicated that scaling has less impact on the resulting Gibbs free energy of formation values. ,, At the suggestion of a reviewer, we investigated this point by computing the effects of scaling frequencies on the thermodynamics of formation of structure T2, the DFT global minimum for Gibbs free energy. Truhlar and co-workers have shown that scaling M08-HX/MG3S harmonic frequencies by a factor of 0.973 yields accurate zero-point vibrational energy (ZPE) values for a comprehensive database of molecules …”
Section: Results and Discussionmentioning
confidence: 99%
“…Scaling harmonic frequencies or calculating anharmonic frequencies is critical for spectroscopists who are trying to locate hydrogen-bonded molecular clusters in their experiments. ,, Yet, previous work has indicated that scaling has less impact on the resulting Gibbs free energy of formation values. ,, At the suggestion of a reviewer, we investigated this point by computing the effects of scaling frequencies on the thermodynamics of formation of structure T2, the DFT global minimum for Gibbs free energy. Truhlar and co-workers have shown that scaling M08-HX/MG3S harmonic frequencies by a factor of 0.973 yields accurate zero-point vibrational energy (ZPE) values for a comprehensive database of molecules …”
Section: Results and Discussionmentioning
confidence: 99%
“…Atmospheric aerosol particles represent the largest uncertainty in our understanding of global climate through their participation in cloud formation and the absorption and scattering of radiation (Kerminen et al, 2005;Kuang et al, 2009;Lohmann and Feichter, 2005;Merikanto et al, 2009;Spracklen et al, 2008). In particular, particle formation by nucleation is still not well understood and is difficult to represent in models (Kerminen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…When performing calculations on clusters where hydrogen bonding plays a key role, it is crucial to keep in mind the importance of scaling harmonic frequencies or calculating anharmonic frequencies. In previous research, we have used Truhlar’s M08-HX/MG3S scaling factor (0.973) and applied it to the thermodynamics of formation for our lowest Gibbs free energy clusters and compared the resulting data to unscaled data. , Our group found the changes in the thermodynamic corrections used to compute the Gibbs free energy of formation to be negligible (about 0.19 kcal mol –1 ), and this conclusion is supported by similar studies. ,, We also checked the effects of applying the quasiharmonic approximation, which applies scaling factors to low-frequency vibrational modes in the partition function, and found no significant effect …”
Section: Resultsmentioning
confidence: 99%